Dependence of polarity inversion on V/III ratio in −c-GaN growth by oxide vapor phase epitaxy. (18th April 2016) - Taniyama, Yuki; Yamaguchi, Yohei; Takatsu, Hiroaki; Sumi, Tomoaki; Kitamoto, Akira; Imade, Mamoru; Yoshimura, Masashi; Isemura, Masashi; Mori, Yusuke
Abstract: One of the issues in bulk c -GaN growth is the decrease in the diameter of crystals with an increase in thickness owing to the appearance of inclined and facets. In this study, we performed − c -GaN growth by oxide vapor phase epitaxy (OVPE). As a result, truncated-inverted-pyramidal crystals were successfully grown on dot-patterned − c -GaN substrates. The diameter of the top surface of crystals was larger than that of windows. We further investigated the dependence of the ratio of inversion-domain area to growth area ( R ID ) on growth temperature, V/III ratio, and growth rate. The remained results revealed that R ID decreased with increasing growth temperature and V/III ratio, and kept constant for growth rate. Additionally, an epitaxial layer on − c -GaN substrates with a growth rate of 12.4 µm/h and an R ID as low as 3.8% was obtained under an NH3 partial pressure ( P NH3 ) of 83 kPa at 1200 °C.